2015
DOI: 10.1016/j.redox.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

NOSH-sulindac (AVT-18A) is a novel nitric oxide- and hydrogen sulfide-releasing hybrid that is gastrointestinal safe and has potent anti-inflammatory, analgesic, antipyretic, anti-platelet, and anti-cancer properties

Abstract: Sulindac is chemopreventive and has utility in patients with familial adenomatous polyposis; however, side effects preclude its long-term use. NOSH-sulindac (AVT-18A) releases nitric oxide and hydrogen sulfide, was designed to be a safer alternative. Here we compare the gastrointestinal safety, anti-inflammatory, analgesic, anti-pyretic, anti-platelet, and anti-cancer properties of sulindac and NOSH-sulindac administered orally to rats at equimolar doses. Gastrointestinal safety: 6 h post-administration, numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 52 publications
(65 reference statements)
0
45
0
Order By: Relevance
“…Such encouraging results may constitute an important breakthrough not only to enrich the quality of life of NSAIDs chronic users, but also to allow the use of these medicines in the therapy of a wider spectrum of diseases. In fact, diverse preclinical studies have been showing the efficacy of phospho‐NSAIDs, NO‐NSAIDs, H 2 S‐NSAIDs, NOSH‐NSAIDs, dual COX/5‐LOX inhibitors, and mPGES‐1 inhibitors as antitumor and/or neuroprotective agents . Therefore, the development of safer anti‐inflammatory drugs may additionally provide valuable options for the long‐term treatment of cancer and neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such encouraging results may constitute an important breakthrough not only to enrich the quality of life of NSAIDs chronic users, but also to allow the use of these medicines in the therapy of a wider spectrum of diseases. In fact, diverse preclinical studies have been showing the efficacy of phospho‐NSAIDs, NO‐NSAIDs, H 2 S‐NSAIDs, NOSH‐NSAIDs, dual COX/5‐LOX inhibitors, and mPGES‐1 inhibitors as antitumor and/or neuroprotective agents . Therefore, the development of safer anti‐inflammatory drugs may additionally provide valuable options for the long‐term treatment of cancer and neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, some proof‐of‐concept animal studies have already shown that NOSH‐derivatives of aspirin, sulindac, and naproxen (Fig. ) exhibit anti‐inflammatory, analgesic, antipyretic, antiplatelet, and antioxidant activities, while sparing the GI tract . For instance, NOSH‐aspirin has displayed superior antinociceptive activity in different animal models of inflammatory pain, as well as greater GI tolerability and antioxidant properties .…”
Section: Association Of Nsaids With Protective Mediatorsmentioning
confidence: 99%
“…The structural components of three of these compounds are shown in Fig 4G-I. In terms of GI safety, NBS-1120 [325], AVT-219 [326], and NOSH-sulindac (AVT-18A) [327] were essentially devoid of any GI toxicity. All three compounds exhibited comparable pharmacological properties to their respective parent compound but unlike their native counterparts were GI safe.…”
Section: Modulation Of H2s Levels As a Strategy To Treat Cancermentioning
confidence: 99%
“…The cell growth inhibitory properties of NBS-1120, NBS-1121, AVT-219, and AVT-18A were evaluated in eleven different human cancer cell lines of six different histological subtypes [325327]. All four NOSH compounds were extremely effective in inhibiting the growth of these cell lines, however, NBS-1120 was the most potent, with IC 50 s for cell growth inhibition ranging from 48–280 nM at 24h [324, 326, 327].…”
Section: Modulation Of H2s Levels As a Strategy To Treat Cancermentioning
confidence: 99%
See 1 more Smart Citation